2016
DOI: 10.1111/jgs.14311
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Lumbar Spinal Stenosis in Individuals Aged 80 and Older: A Multicenter Observational Study

Abstract: Individuals aged 80 and older experience improvement in self-reported outcomes similar to those of younger individuals after decompressive surgery for LSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
1
22
0
3
Order By: Relevance
“…A previous study on a similar population from the NORspine registry showed no difference in outcomes between non-responders and responders [21]. The minor differences in baseline characteristics between non-responders and responders at 1 year are not likely to influence our results [7,[13][14][15]. Also, we are lacking data on exact amounts of costs, payment, and reimbursements, inhibiting us from performing cost-effectiveness analyses.…”
Section: Study Strengths and Limitationsmentioning
confidence: 77%
“…A previous study on a similar population from the NORspine registry showed no difference in outcomes between non-responders and responders [21]. The minor differences in baseline characteristics between non-responders and responders at 1 year are not likely to influence our results [7,[13][14][15]. Also, we are lacking data on exact amounts of costs, payment, and reimbursements, inhibiting us from performing cost-effectiveness analyses.…”
Section: Study Strengths and Limitationsmentioning
confidence: 77%
“…LSS is more common in the geriatric population and in many studies the mean age of the sample size is more than 65 years. Recent studies which have compared traditional surgery to BDUA for patients aged 80 years and older have demonstrated that there were no between-group differences in duration and outcome results of the surgical procedures (9). In the current study, unlike previous studies, patients were separated according to age as an elderly group (>60 years) and an adult group (<60 years).…”
Section: Limitationsmentioning
confidence: 88%
“…In the study by Rihn et al, 10 only 8.6% (n = 5) of the octogenarians underwent instrumented fusion, hence limiting further subgroup analysis for a fusion-only cohort. The clinical success of lumbar decompression surgery in the octogenarian population has been further established in studies by Giannadakis et al, 11 Galiano et al, 12 and Shabat et al 13 However, it is important to note that these studies address lumbar decompression, but do not address the viability of fusion, which highlights the need to better understand the role of lumbar fusion in the octogenarian population from both a clinical and operative standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…2–5 Several studies have demonstrated an increase in lumbar surgical intervention (decompression and/or fusion) in the broadly termed elderly population over the past 20 years. 2,3,68 Other studies have investigated safety and efficacy of lumbar spine surgery in this age group, with results showing both benefits 913 and risks. 14 However, no prior study has specifically identified national trends in the use of lumbar fusion surgery for the octogenarian population, with respect to demographics, discharge time, and economic impact.…”
Section: Introductionmentioning
confidence: 99%